Ag6Cu8(C=CAr)14(DPPB)2: A Rigid Ligand Co‐Protected Bimetallic Silver(I)‐Copper(I) Cluster with Room‐Temperature Luminescence - Jin, Jun‐Ling; Zhang, Sheng‐Fa; Zhao, Pei; Shen, Yang‐Lin; Fang, Jun‐Jie; Liu, Zheng; Ehara, Masahiro; Mi, Li‐Wei; Xie, Yun‐Peng; Lu, Xing (Chemistry, an Asian journal, 2023)
Metal clusters have become increasingly important in various applications, with ligands playing a crucial role in their construction. In this study, we synthesized a bimetallic cluster, Ag6Cu8(C=CAr)14(DPPB)2 (Ag6Cu8), using a rigid acetylene ligand, 3,5‐bis(trifluoromethyl)phenylacetylide. Through single‐crystal structure characterization, we discovered that the butterfly‐shaped Ag2Cu2 motifs were subject to distortion due to steric hindrance imposed by the rigid ligand. These motifs assembled together through shared vertices and edges. Mass spectrometry analysis revealed that the primary fragments detected during electrospray ionization (ESI) testing corresponded to the Ag2Cu2 motifs. Furthermore, we conducted a comprehensive investigation of the cluster's solution properties employing 31P NMR, UV‐vis absorption, and photoluminescent measurements. In contrast to previously reported Ag/Cu bimetallic clusters protected by flexible ligands, Ag6Cu8 protected by rigid ligands exhibited intriguing room temperature fluorescence properties alongside excellent thermal stability. DFT calculations on Ag6Cu8 and Ag6Cu8 with the rigid aromatic ring removed revealed that the presence of the rigid aromatic ring can lower the electronic energy levels of the cluster, and reduce the energy gap from 4.05 eV to 3.45 eV. Moreover, the rigid ligand further suppressed the non‐radiative transition process, leading to room temperature fluorescence emission. A new atomically precise cluster Ag6Cu8(C=CAr)14(DPPB)2 has been prepared by utilizing rigid alkynyl ligands. These rigid ligands impart the bimetallic cluster with high stability and a distinct red emission at room temperature. The proposed mechanism is that the phenyl groups on the peripheral C=C−Ar ligands contribute to the reduction of energy levels and energy gaps within cluster.